PENGARUH DISIPLIN KERJA TERHADAP PELAYANAN RAWAT INAP DI RSUD ARIFIN NU’MANG KECAMATAN PANCA RIJANG - Irfan Lukman; Ahmad, Jamaluddin (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to examine the effect of work discipline on the quality of inpatient services at Arifin Nu'mang Hospital, Panca Rijang District. This study uses a quantitative approach with a descriptive associative research type. Data collection was carried out by observation, questionnaires, and documentation. Data analysis used simple linear regression with the SPSS version 22 program. The results showed that work discipline had a significant effect on the quality of service with a significance value of 0.000 (<0.05) and t count 10.720> t table 2.021. The coefficient of determination (R²) of 0.742 indicates that work discipline contributed 74.2% to the variance in the quality of inpatient services. The results of this study indicate that increasing employee discipline, especially those related to punctuality, responsibility, and professional ethics, can significantly improve hospital service performance.